Palam Eat / Naim Junaidi Kamal Apandi and Danish Danial Mohd Sham - Kamal Apandi, Naim Junaidi; Mohd Sham, Danish Danial (2023)
This social media portfolio report will focus on how Palam Eat has utilised Facebook for online advertising purposes. Naim Junaidi and Danish Danial are in charge of the Palam Eat dessert resale business at UiTM Puncak Alam while they complete the project evaluation. The corporation used teaser and copywriting— comprising both the hard sell and the soft sale, respectively—on its Facebook page to promote and advertise the product to the public.